Feasibility of Treated Sand Brick Waste with Silica Fume Based Geopolymer for Coarse Aggregate Application - R. Abd Razak; A.N.D. Kiong; M.M. Al Bakri Abdullah; Md A.O. Mydin; A.V. Sandu; Z. Yahya; A. Abdullah; P. Risdanareni; E. Arifi (Archives of Metallurgy and Materials)
Construction and demolition waste (CDW) management should focus on reducing CDW or properly recycling the materials since this waste is now a global problem. Sand brick waste, a component of a building’s structure, is one type of CDW. To be used as recycled aggregate, these wastes are invariably categorised as low grade. Due of the improved qualities provided, geopolymer research has recently become more popular. The objective of this study is to investigate the physical and mechanical properties of recycled sand brick aggregate (RSB) treated with silica fume based geopolymer coating. Additionally, the effectiveness of the treated RSB will be applied in concrete as coarse aggregate. The sample was made using a solid-to-liquid ratio of 1.0, 1.2, 1.4, 1.6, and 1.8. At 2.5 and 10 M, alkaline activator is a constant variable. Testing of specific gravity, water absorption, and aggregate impact value were analysed. The treated RSB concrete will then be evaluated against normal concrete. In terms of density, water absorption, and compressive strength, natural concrete performs better than treated RSB concrete. In comparison to natural concrete, treated RSB concrete absorbs 5.8% more water. Treated RSB concrete has a density of 1815 kg/m3, compared to natural concrete’s 2080 kg/m3. The compressive strength of concrete made using treated RSB aggregate is 18.1 MPa after 7 days, and 27.1 MPa at 28 days. The testing revealed that the treated RSB aggregate concrete met the specifications. As a result, treated RSB aggregate concrete offers an advantage over natural OPC concrete while saving the environment.